PENGARUH CITRA INSTITUSI DAN KUALITAS LAYANAN TERHADAP KEPUASAN DAN LOYALITAS MAHASISWA UNIVERSITAS MOCH. SROEDJI JEMBER - Noviasari, Rifka Arinda; Wulandari, Deasy; Suryaningsih, Ika Barokah (BISMA: Jurnal Bisnis dan Manajemen, 2015)
Abstract: The purpose ofthis study was to examine the effect of institutional image and service quality on satisfaction and loyalty of students of the Moch. Sroedji Jember University. A total of 144 students was used as the sample. The hypothesis were tested using Structural Equation Modelling. Results show that institutional image and service quality affect student satisfaction and loyalty significantly. Customer satisfaction affects customer loyalty significantly. Keyword: Institutional Image, Service Quality, Satisfaction, and Loyalty.